Investigation of potential antibiofilm properties of Antimicrobial Peptide (AMP) from Linckia laevigata against Candida albicans: An in vitro and in vivo study. (December 2020) - Siddharthan, Seema; Rajamohamed, Beema Shafreen
Graphical abstract: Highlights: In silico prediction of AMP from L. laevigata . In vitro and in vivo evaluation for biofilm and toxicity using zebrafish embryos. Peptides were represented as promising candidate to treat C. albicans biofilm. Abstract: Biofilm-associated Candida albicans infection remains to be challenging, though there are several investigations and developments in the medical therapy. Antimicrobial peptides are promising candidates due to their efficacy to target pathogens and cancer cells. In the present study, LLpepII identified from Linckia laevigata (star fish), has been predicted as ɑ-helical, amphipathic antimicrobial peptide. LLpepII was investigated for their potency to inhibit C. albicans biofilm formation using crystal violet. LLpepII shows antibiofilm activity which inhibits only the biofilm formation and without inhibiting the growth of the yeast cells. This biofilm specific activity of LLpepII was confirmed through SEM and XTT assay. Cell viability assay revealed that LLpepII significantly inhibited the proliferation of human cervical (HeLa) cell lines. Morphological changes in HeLa cells, apoptosis and cell death was studied using AO/EB. It is also confirmed that LLpepII can prevent infection and it is non toxic using zebrafish egg infection model. These results suggest that amphipathic LLpepII as promising candidate with dual property can be explored further as antibiofilm and antiproliferate candidate for therapeutic applications.